Chicken feather keratin in the properties of corn-glycerol starch biofilms - Costa, Djeson Mateus Alves da; Oliveira, Raniely Alves de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Biodegradable plastics based on starch have acquired considerable importance in view of their possibility of replacing the conventional plastics derived from fossil sources. The aims of this research was to evaluate the effect of the addition of keratin (0, 10 and 20%, relative to the amount of starch) from chicken feathers on the properties of corn-glycerol starch biofilms. Films is obtained by casting and the tests to obtain and characterize them were conducted in the physicochemical and chemical processes laboratories from Federal Institute of Education, Science and Technology of Rio Grande do Norte, Campus Nova Cruz. The parameters thickness, weight, density, transparency, humidity, water solubility and biofilms water vapor permeability were evaluate. The values of transparency, thickness, weight and density of the films no affected with treatments applied. The water solubility and the water vapor permeation rate of the films reduced with increasing amount of keratin.